2008
DOI: 10.1007/s10926-008-9121-8
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review of the Factors which Predict Return to Work for People Suffering Episodes of Poor Mental Health

Abstract: Introduction Poor mental health is responsible for a large percentage of long term work absence, and only 50% of those who are off work for 6 months or more return to work. Method We aimed to describe the factors which predict or restrict return to work for people suffering episodes of poor mental health. A literature review was conducted to identify all papers relating to long term mental illness absence. Results Fourteen papers of varying methodological quality considered mental health in relation to psychia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

17
170
3
6

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 191 publications
(196 citation statements)
references
References 21 publications
17
170
3
6
Order By: Relevance
“…In general, more severe mental health complaints are predictive of less favourable RTW outcomes (see for a review [15]). Moreover, several studies have identified symptom severity as a significant predictor for less favourable mental health outcomes of CBT.…”
Section: Influence Of Mental Health Symptoms On Treatment Successmentioning
confidence: 99%
See 2 more Smart Citations
“…In general, more severe mental health complaints are predictive of less favourable RTW outcomes (see for a review [15]). Moreover, several studies have identified symptom severity as a significant predictor for less favourable mental health outcomes of CBT.…”
Section: Influence Of Mental Health Symptoms On Treatment Successmentioning
confidence: 99%
“…We assume that this would be particularly true for W-CBT techniques, whereby individuals are stimulated to focus on work and (partial) RTW. Individuals with high baseline anxiety and depressive complaints generally experience a less favourable RTW process [15]. Individuals may also fear that early RTW would be hampered by, or may even aggravate, their mental health symptoms [12,31].…”
Section: Influence Of Mental Health Symptoms On Treatment Successmentioning
confidence: 99%
See 1 more Smart Citation
“…Blank et al 1 have shown that between 1985-2005 in North America and England, only 50% of those who took leave of absence from work due to mental disorders for more than six months returned to work.…”
Section: Introductionmentioning
confidence: 99%
“…To understand the complexity of this problem, some authors have studied predictors of return to work, which include different sorts: personal, environmental, organizational and relational 1 . Based on the latter, Nielsen et al 2 (p. 807) presented the "expectations about the return to work" as a return to work predictor.…”
Section: Introductionmentioning
confidence: 99%